Imitation and Society : The Persistence of Mimesis in the Aesthetics of Burke, Hogarth, and Kant - Huhn, Tom (Book collections on Project MUSE., 2004)
Mimesis also thereby became enmeshed in the ideas of sociality contained, often only implicitly, within the new accounts of aesthetic judgment." "The book proceeds by reading three of the foundational treatises in aesthetics - Burke's Philosophical Enquiry into the Origin of Our Ideas of the Sublime and Beautiful, Hogarth's Analysis of Beauty, and Kant's Critique of Judgment - with an eye for discerning where arguments and analyses betray mimetic structures. Huhn attempts to explicate these books anew by arguing that they are pervaded by a mimetic dynamic. Overall, he seeks to provoke a reconsideration of eighteenth-century aesthetics that centers on its continuity with traditional notions of mimesis."--Jacket.